Réécrire l'Histoire pour les enfants du point de vue des Amérindiens : devoir de mémoire, devoir d'imagination (Brésil, États-Unis) - Pauline Franchini (Amnis)
In historical novels for children, History is often a pretext, an exotic background in front of which adventure stories unfold. This couldn't be the case in historical novels dealing with colonial and pre-colonial times, most of all those written by native american or afro-descendant writers affected by postcolonial issues: in these novels, the interpretation of historical events according to the point of view in which it is narrated – often that of the vainquished - is crucial. Fictions depicting the encounter – imminent or recent – between Europeans and indigenous american people, through the eyes of the latter, change children's standpoint to History's off-camera and offer alternatives to the official version. The ability to identify to heroes or main characters, which caracterizes children's novels, takes a political dimension, insofar as, made extraneous to him or her, the young reader experiences otherness, the relativity of values and of History's wrongs. Fiction becomes – paradoxically – a mean to access History's concealed truth and to denounce it, aswell as its secrets, as a fiction itself, should we think about the myth of « discovery », to the glorification of pioneers and to the stereotypes spread about americindians. Edwidge Danticat and Louise Erdrich in the United States of America, Daniel Munduruku and Joel Rufino dos Santos in Brazil, are a part of these writers who put their talent to the service of the duty of remembrance, which is also a duty of imagination.